Strategies and Measures to Prevent Spread of Invasive Species - Darrigran, Gustavo Alberto (2015)
On the basis of the fouling caused by the golden mussel, Limnoperna fortunei, in industrial facilities and power plants (human environment), and its impacts on the ecosystem (natural environment), several strategies and measures for the mitigation of problems and prevention of further spread are discussed. At the local level, monitoring and early detection of the golden mussel can be accomplished through different methods, including those aimed at juveniles and adults, and also those aimed at their planktonic larvae. Priorities for designing bioinvasion management strategies should focus on generation of scientific knowledge, management, and actions at the sociopolitical level. Mitigation measures are closely related to the invasion phase, whereby the cost increases and the probability of eradication decreases over time.